Experimental investigation on the effect of porous-fin position in a thermal energy storage tank for performance enhancement of the system - C. Suresh; Awasthi Abhishek; Binit Kumar; Yongseok Jeon (Case Studies in Thermal Engineering)
Metal foam plays a significant role in the heat transfer augmentation of phase change material (PCM)-based thermal applications. Although incorporating metal foam in thermal systems will increase the thermal conductivity, it will also mitigate the natural convection as a result of the metal foam structure and in turn lower the thermal performance. Non-uniform temperature distribution in thermal energy storage (TES) represents another major problem in thermal management applications. To overcome this issue of non-uniformity in temperature as well as improve convective heat transfer and energy storage capacity, the current study proposes incorporating porous-fins at different locations of TES. To this end, four cases—i.e., Case-1 (pure PCM without-fin), Case-2 (porous-fin at top), Case-3 (porous-fin at middle), and Case-4 (porous-fin at bottom)—were designed and experimentally assessed to compare their thermal performances. The experimental results revealed that Case-2, Case-3, and Case-4 exhibited reductions in the melting time of PCM of 16.65 %, 29.63 %, and 45.83 %, respectively, compared to Case-1. Further, Case-4 showed higher cumulative energy transfer, uniform melting, and temperature distribution than the other cases. Based on the obtained performance parameters, it was concluded that Case-4 has superior performance and is an optimized case compared to the other cases.